Pengaruh Latihan Senam dan Daya Tahan Tubuh terhadap Respon Nyeri Haid (Dysmenorrhea) - Puspita Sari, Ika Endah; Rumini, Rumini; Mukarromah, Siti Baitul (Journal of Physical Education and Sports, 2017)
Penelitian bertujuan untuk mengetahui: (1) perbedaan pengaruh antara senam pilates dan yoga terhadap respon nyeri haid (dysmenorrhea); (2) perbedaan pengaruh antara daya tahan tubuh tinggi dan daya tahan tubuh rendah terhadap respon nyeri haid (dysmenorrhea); (3) interaksi antara senam dan daya tahan tubuh terhadap respon nyeri haid (dysmenorrheal). Penelitian ini menggunakan metode eksperimen dalam rancangan faktorial 2x2. Teknik pengambilan sampel dengan teknik purposive sampling yaitu sebanyak 20 orang dari total populasi 27 orang siswa kelas X. Teknik analisis data digunakan uji ANOVA dua jalur dengan program SPSS 20 dan taraf signifikansi 5%, dilanjutkan dengan uji tukey. Hasil analisis data diperoleh jawaban hipotesis 1 yaitu terdapat perbedaan pengaruh antara senam pilates dan yoga terhadap respon nyeri haid dengan keterangan nilai Fhitung > Ftabel atau 74,462 > 4,20 dan nilai signifikansi 0,000 < 0,05. Hipotesis 2 yaitu terdapat perbedaan pengaruh antara siswa yang memiliki daya tahan tubuh tinggi dan rendah terhadap respon nyeri haid dengan keterangan Fhitung>Ftabel atau 138,462 > 4,20 dan nilai signifikansi 0,000 < 0,05. Hipotesis 3 yaitu terdapat interaksi antara senam dan daya tahan tubuh terhadap respon nyeri haid dengan keterangan Fhitung > Ftabel atau 5,538 > 4,20 dan nilai signifikansi 0,032 < 0,05. Uji tukey untuk perbandingan antar variabel dan diperoleh hanya 2 yang tidak memiliki perbedaan yaitu kelompok senam pilates dan tingkat daya tahan tubuh tinggi dengan senam yoga dan tingkat daya tahan tubuh tinggi dengan keterangan qhitung (1,520) < qtabel (2,27), dan untuk senam yoga pada daya tahan tubuh tinggi dengan senam pilates pada daya tahan tubuh rendah dengan keterangan qhitung (0,760) < qtabel (2,27).This study aims to determine: (1) the difference between the influence of gymnastics pilates and yoga on the response of painful menstruation (dysmenorrhea); (2) the difference between the effect of high endurance and low immune response against painful menstruation (dysmenorrhea); (3) the interaction between exercise and endurance to the response of painful menstruation. This study used an experimental method in a 2x2 factorial design. The sampling technique sampling techniques purposive as many as 20 people from a total population of 27 students of class X. The data analysis technique used ANOVA test two lanes with SPSS 20 and significance level of 5%, followed by Tukey test. Results of data analysis obtained one answer hypothesis that there is a difference between the effects of pilates and yoga exercises against menstrual pain response with the information value of Fvalue > Ftable or 74.462 > 4.20 and a significance value 0.000 < 0.05. Hypothesis 2 that there is a difference of influence between students who have high endurance and low against menstrual pain response with the description of Fvalue > Ftable or 138.462 > 4.20 and a significance value 0.000 < 0.05. Hypothesis 3 that there is interaction between gymnastics and endurance against menstrual pain response with the description of Fvalue > Ftable or 5.538 > 4.20 and a significance value of 0.032 < 0.05. Tukey test for comparison between variable and obtained only two that do not have a difference in the gymnastics group pilates and endurance levels high with yoga exercises and endurance levels high with a description qvalue (1,520) < qtable (2.27), and for gymnastics yoga on a high endurance with pilates exercises on low immunity with information qvalue (0.760) < qtable (2.27). The conclusions of this research are: (1) there is a difference between the effects of pilates and yoga exercises on response to painful menstruation (dysmenorrhea), gymnastics pilates give better effect; (2) there is a difference between the effects of endurance of high and low immune response against pain (dysmenorrhea), and students who have a high durability is better; (3) There is no interaction between gymnastics and endurance to the response of painful menstruation (dysmenorrhea). Suggested gymnastics pilates and yoga can be applied to reduce menstrual pain response, this is because of both the exercisers had a good change to the conditions of the student menstrual pain.